Design of Conformal Microstrip Patch Antenna for Vehicle Tracking - Ebenezer Abishek, B; Abdul Hashim, Z; Sai Prasath, Hari; Arul Stephen, C; C. Kishore Kumar, P (International Journal of Engineering and Technology, 2018)
The road accidents have increased in the urban areas to the level which is alarming. The accidents cause loss of human life which can be avoided if the accident victim is rescued at the earliest and given the necessary treatment. This paper involves the designing of an antenna unit for the purpose of tracking the vehicles met with the accidents. The tracking unit placed in vehicles requires a low profile antenna to be placed on top of the roof of vehicle. The simulation study of this antenna is performed in Feko Suite and validated in CST.Â